2017
DOI: 10.1002/adem.201600612
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Raman Spectroscopy Using Nanofocusing of Light

Abstract: Raman spectroscopy is uniquely sensitive to crucial material properties like stress and composition, but is inherently diffraction-limited, impeding its application potential in nanostructured devices. Under correct polarization conditions, the Raman response from a periodic array of fins is dramatically enhanced inside the semiconductor material, re-enabling fast and non-destructive optical characterization of deep-subwavelength semiconductor patterns. In this paper, it is shown that the effect is not limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…By exploiting the underlying physics of the characterization methods, it has been possible to isolate the information of the devices from the surrounding matrix. The study of embedded nanostructures using ensemble measurements has already been reported for small-angle x-ray scattering, for grazing-incidence x-ray fluorescence, 7 for medium energy ion scattering, 8 for Raman spectroscopy, 9 and for secondary ion mass spectrometry. 10 In the present work, we will present the developments required to extend this approach toward Rutherford backscattering spectrometry (RBS).…”
Section: Introductionmentioning
confidence: 99%
“…By exploiting the underlying physics of the characterization methods, it has been possible to isolate the information of the devices from the surrounding matrix. The study of embedded nanostructures using ensemble measurements has already been reported for small-angle x-ray scattering, for grazing-incidence x-ray fluorescence, 7 for medium energy ion scattering, 8 for Raman spectroscopy, 9 and for secondary ion mass spectrometry. 10 In the present work, we will present the developments required to extend this approach toward Rutherford backscattering spectrometry (RBS).…”
Section: Introductionmentioning
confidence: 99%
“…stress to be measured in nanometer-scale fin field-effect transistors (finFETs) with Raman spectroscopy. 6,9,10 However, these previous studies were limited to single arrays of lines and consequently could not be applied after the replacement gate processing of modern GAA transistors, when two perpendicular gratings are processed on top of each other with the top grating being made of 150−200 nm thick amorphous Si lines. 11,12 The present paper extends our previous studies and demonstrates that the nanofocusing effect is also of application in systems constituted of two perpendicular gratings.…”
mentioning
confidence: 99%
“…The strongly enhanced signal-to-noise ratio allowed e.g. stress to be measured in nanometer-scale fin field-effect transistors (finFETs) with Raman spectroscopy. ,, However, these previous studies were limited to single arrays of lines and consequently could not be applied after the replacement gate processing of modern GAA transistors, when two perpendicular gratings are processed on top of each other with the top grating being made of 150–200 nm thick amorphous Si lines. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new group of techniques has emerged which are based on the principle of the ensemble measurement. This is the simultaneous measurement of a large ensemble of structures and leads to an enhanced sensitivity [8][9][10][11][12][13][14][15] . It is enabled by the excellent uniformity of the nano-scale patterns produced by semiconductor manufacturing [16][17][18] , characterized by a standard deviation on the size of the nanostructures of the order of 1 nm.…”
mentioning
confidence: 99%